2011
DOI: 10.1002/jcop.20476
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood disorder and the sense of personal control: which factors moderate the association?

Abstract: This study examines whether and how select individual characteristics moderate the relationship between neighborhood disorder and a sense of personal control. Our findings show that neighborhood disorder is associated with a decreased sense of control. However, regression analyses including interaction terms of neighborhood disorder and some individual characteristics show that the negative effect of neighborhood disorder on sense of control is greater among Whites and people with low economic hardship, compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 36 publications
0
30
2
Order By: Relevance
“…Previous research has not investigated the compound disadvantage model of neighborhood effects on mastery. One study found the opposite (i.e., compound advantage) when investigating neighborhood stressors as an individual‐level construct (Kim & Conley, ), but these results may be specific to the effects of individually reported neighborhood stressors, rather than more objectively measured ones, or to the racially segregated context of Chicago.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has not investigated the compound disadvantage model of neighborhood effects on mastery. One study found the opposite (i.e., compound advantage) when investigating neighborhood stressors as an individual‐level construct (Kim & Conley, ), but these results may be specific to the effects of individually reported neighborhood stressors, rather than more objectively measured ones, or to the racially segregated context of Chicago.…”
Section: Discussionmentioning
confidence: 99%
“…Schwartz and Meyer (2010) have recently criticized the literature testing the stress process because of researchers’ reliance on within‐group analyses in relatively homogenous samples. In one exception, Kim and Conley () found, in a sample of English‐speaking adults in Illinois, that Whites have a stronger association between perception of neighborhood disorder and sense of personal control than non‐Whites. Although these findings do not support the compound disadvantage model I propose here, Kim and Conley () conceptualize neighborhood disorder as an individual perception rather than a neighborhood characteristic.…”
Section: Neighborhood Compound Disadvantagementioning
confidence: 99%
“…Indeed, perception was significantly associated with the alcoholism in adulthood and mediated the association between neighborhood SES and alcoholism in an adult‐limited model. The importance of perception may reflect the role of felt control, and the distress that lack of control may impart, in determining the effect of neighborhood context on alcohol use and other health problems (Hill & Angel, ; Kim & Conley, ).…”
Section: Discussionmentioning
confidence: 99%
“…The participants were homogenous, French‐speaking North Americans of European descent. Future research should be conducted in a more heterogeneous population to establish whether these associations persist across race and ethnicity (Kim & Conley, ).…”
Section: Discussionmentioning
confidence: 99%
“…shows that individuals living in stressful and highly disordered neighborhoods experience a low sense of personal control (e.g., Geis & Ross, 1998;Kim & Conley, 2011;Ross & Mirowsky, 2009). Stressful life events, in particular those that are negative and uncontrollable such as crime and danger in the neighborhood, can lower one's belief in their ability to influence their life circumstances .…”
Section: Personal Controlmentioning
confidence: 99%